2012
DOI: 10.1128/jvi.00325-12
|View full text |Cite
|
Sign up to set email alerts
|

Activating KIR Copy Number Variation Is Associated with Granzyme B Release by NK Cells during Primary Simian Immunodeficiency Virus Infection in Rhesus Monkeys

Abstract: Here we show that the number of activating killer cell immunoglobulin-like receptor (KIR) copies in rhesus monkeys is associated with the extent of release of cytotoxic granules by cytolytic NK cells during primary simian immunodeficiency virus SIVmac251 infection. These findings suggest that NK cells expressing high levels of activating KIRs efficiently kill SIVmac251-infected cells, and this efficient killing contributes to the NK cell-mediated control of replication of this virus during early infection. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…It has been long established that particular macaque MHC class I alleles are associated with differential outcomes in experimental disease settings , but it is only in recent years that KIR has been studied in this context. On a modest scale compared with human studies in terms of numbers of subjects tested, similar sorts of KIR associations have been made in the simian immunodeficiency virus (SIV) model in rhesus macaques , which is studied in the context of AIDS vaccine research. In essence, these studies have demonstrated that NK cells play an important role in the containment of SIV infection but also that particular KIR‐MHC combinations determine either a poor or a good prognosis, as is reflected by a high or low viral load, respectively.…”
Section: Kir Disease and Reproductive Successmentioning
confidence: 94%
“…It has been long established that particular macaque MHC class I alleles are associated with differential outcomes in experimental disease settings , but it is only in recent years that KIR has been studied in this context. On a modest scale compared with human studies in terms of numbers of subjects tested, similar sorts of KIR associations have been made in the simian immunodeficiency virus (SIV) model in rhesus macaques , which is studied in the context of AIDS vaccine research. In essence, these studies have demonstrated that NK cells play an important role in the containment of SIV infection but also that particular KIR‐MHC combinations determine either a poor or a good prognosis, as is reflected by a high or low viral load, respectively.…”
Section: Kir Disease and Reproductive Successmentioning
confidence: 94%
“…Seventy‐three individuals were characterized for KIR copy number profiles. Thirty‐six copy number profiles were found; (a) usual KIR copy number, (b) expanded copy number profiles, (c) contracted copy number profiles . [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
“…Seventy-three individuals were characterized for KIR copy number profiles. Thirty-six copy number profiles were found; (a) usual KIR copy number, (b) expanded copy number profiles, 26,40 (c) contracted copy number profiles. 26 KIR3DP1 and 2DL4, that typically present with two copies, were found at one, three or four copies in 1Á4-5Á5% of NETs.…”
Section: Kir Genotypes In Netsmentioning
confidence: 99%
See 2 more Smart Citations